Managing Patients with Chronic Pain and Opioid Addiction - Taylor, Donald R. (Springer International Publishing : Imprint: Adis, 2015)
This text will provide readers with a thorough review of the complex condition of chronic pain and addictions. The book was originally commissioned due to the need in the field for more literature on the topic. This concise pocket book will review epidemiology, clinical features, diagnosis, and medical management of both chronic pain and addiction. Busy healthcare professionals will benefit from this text, which will not only cover the foundation of the management of both conditions and together, but discuss up-to-date national and international treatment guidelines, upcoming therapies and REMS.